EXTREME LOW BIRTH PARAMETER NEONATES WOULD MORE READILY DIE OF HYPERTHERMIA THAN HYPOTHERMIA IN NIGERIA - Olutunde,OE; Oyedokun,A; Olateju,EK; Ibekwe,MU; Kawuwa,MB; Alabi,P; Amadi,HO (2015)
Objective: To investigate how thermal instability might have contributed to a record high neonatal mortality of extreme low birth weight (ELBW) babies in Nigeria.Methods: Ninety-two previous cases from three Nigerian tertiary hospitals were analysed. The average birth weight of the sample population was 993g ± 256g; range: 600g to 1500g from which the ELBW cases (mean: 846g ± 128g; range: 600g to 1000g) were isolated. A temperature-time graph with clearly visible thermal safe-zone band was developed from which all fatality-associated thermal instabilities were identified and defined based on their characteristic consistencies. Parametric quantifications for these were devised to enable the definition of critical values. This was applied to all cases in the sample population to identify and quantify a measure of the various thermal distresses that might have contributed or led to neonatal death. Algorithm-based thermal control technique was devised and results from surviving cases compared.Findings: Hypothermic complications were prevalent with a fatality rate of 22.7% and associated with 65% of all deaths. Hyperthermic related complications accounted for 35% of all deaths but with a higher fatality rate of 64.3%. All babies that experienced prolonged hypothermia that culminated in a sharp flip to hyperthermia survived. However all those that experienced prolonged hyperthermia culminating in a sharp flip to hypothermia died within 12 hours of the event. Algorithm-based patients did not experience this flip.Conclusion: Hyperthermia will more readily kill neonates; hence methods of quenching high and prolonged fever must be reviewed.